Perancangan Checklist untuk Monitoring Progress Report Implementasi ISO 9001:2015, ISO 22000:2018, ISO/TS 22002-1 dan Additional FSSC V.5 2019 - Willy Suryaputra; i Nyoman Sutapa (Jurnal Titra, 2020)
A manufacture company that produces palm oil. The company has various kinds of certifications, the focus of this design is ISO 9001: 2015, ISO 22000: 2018, ISO / TS 22002-1 and add FSSC V.5 2019. These four certifications are used to carry out internal audits. In conducting an internal audit, it is necessary to monitor the non conformity, so that they know the status of the non conformity whether they have been improved or are still in process or have not been improved. Monitoring activities use progress report documents. The progress report document contains a checklist that contains the clauses of the four certifications, contains the final grades based on each section, each department and each clause and shows the number of findings according to status. The results of the internal audit in July obtained a final grade of 89.93% and there were 92 non conformity. Non conformity with the status of Done amounted to 80 non conformity, the status of In Progress amounted to 3 non conformity and the status of Delayed amounted to 9 non conformity.